The impact of extended pulp chamber preparations on the clinical performance of endocrowns in Indian patients: A 1-year observational study - Preethi Duraisamy; Naveen Gopi Chander; Jetty Ramesh Reddy; Muthukumar Balasubramanium (Journal of Oral Biology and Craniofacial Research)
Purpose: The limitations of foundation restorations have been reduced with the advent of endocrowns. Despite their success, the extent of endocrowns tooth preparation into the pulp chamber has not been fully explored in the literature. The study aimed to evaluate the clinical performance of endocrowns with 5 mm extended pulp chamber tooth preparations in Indian patients over a 1- year period using modified USPHS criteria. Methods: The observational study recruited 36 participants with definite criteria. Ceramic crown was planned for all the participants. Conventional endocrown tooth preparation was made with 5 mm pulpal extension. Clinical assessments were made at 0-, 6- and 12-months intervals using modified USPHS criteria. The data was statistically analyzed using Friedman test and Wilcoxon signed rank test. Results: One patient (2.8%) experienced loss of retention, marginal adaptation, and loss of anatomical form during 1-year follow up period. The majority of the participants (97.3%) reported no discomfort and high satisfaction. (P < .05) No opposing tooth wear was observed at 0- and 6-months. The results showed statistical significance in the parameters of retention, marginal adaptation, loss of anatomical form, and patient satisfaction. (P < .05). Conclusion: The clinical performance of endocrowns with extended pulp chamber preparation was satisfactory for a period of 12 months.